A single‐center experience of cytomegalovirus infections in Asian pediatric patients undergoing allogeneic hematopoietic stem cell transplant for leukemia in Singapore. Issue 4 (23rd May 2014) - Tan, P.L.; Lim, L.M.; Khanlian, C.; Villegas, M.S.
Abstract Introduction Cytomegalovirus (CMV) infection remains a significant cause of morbidity and mortality in pediatric patients undergoing allogeneic hematopoietic stem cell transplantation (HSCT) despite improved surveillance and the current preemptive approach. Few data on its prevalence in the Asian pediatric population exist. Methods We retrospectively reviewed the prevalence of CMV infections in 33 patients with 37 transplants who received HSCT for leukemia from 1998 to 2008, and who were managed preemptively for infections. Results In the 37 transplants, 16 patients (43%) had CMV DNAemia. Of the patients who were CMV seropositive before transplant and received stem cells from seropositive donors (R+/D+), 69% had DNAemia; of those who received stem cells from seronegative donors (R+/D−), 36% had CMV DNAemia. Of the patients who were CMV naïve before transplant and received stem cells from seropositive donors (R−/D+), 25% had CMV DNAemia. In CMV‐seronegative donor–recipient transplants (R−/D−), 20% of patients had CMV DNAemia. The median time to the first episode of CMV DNAemia was 21 (range: 10–107) days after the transplants, and the median duration of CMV DNAemia was 22 (range: 2–315) days. CMV DNAemia recurred in 44% (7 of 16) of these patients. Only 1 patient developed CMV disease (retinitis). No deaths were related to CMV infections. Conclusions CMV infection manifesting as DNAemia is a common complication in pediatric patients undergoing allogeneic HSCT for leukemia. Pre‐transplant serostatus predicts reactivation risks; invasive CMV disease is rare using the preemptive approach in our patient population.